Progressive accumulation of cytoplasmic aggregates in PRPF31 retinal pigment epithelium cells interferes with cell survival. Issue 4 (8th December 2022) - Georgiou, Maria; Atkinson, Robert; Mozaffari‐Jovin, Sina; Lako, Majlinda
Abstract: Retinitis Pigmentosa (RP) is a common form of inherited degenerative disease that often leads to blindness. About 10% autosomal dominant RP cases have been associated with mutations in PRPF31 gene, which is involved in pre‐mRNA splicing. This commentary summarises the key findings of our recent publication 'Activation of autophagy reverses progressive and deleterious protein aggregation in PRPF31 patient‐induced pluripotent stem cell‐derived retinal pigment epithelium cells' in the context of large cytoplasmic aggregates which accumulate progressive with time and impair cell function and survival. Understanding the pathomechanism of PRPF31‐RP provides invaluable information that can be used to understand other PRPF‐RPs, and help to design effective and appropriate therapeutic strategies for the treatment of RP patients with PRPF31 mutations. Abstract : Schematic representation showing mislocalisation of mutant PRPF31 in the cytoplasm of PRPF31‐retinitis pigmentosa (RP) cells and accumulation of aggregates containing HSPs, visual cycle and ubiquitin conjugated proteins due to autophagy and proteasome dysfunction. Large cytoplasmic aggregates accumulate gradually in the cytoplasm of PRPF31‐RP and cause cell toxicity and stress, impaired cellular structure and function and reduce cell survival (left panel). Administration of Rapamycin activates autophagy and reduces cytoplasmic aggregates. However, to restore PRPF31 expression and splicing activity, gene supplementation using AAV.PRPF31 is necessary (right panel). HSPs, heat shock proteins; m, mutant PRPF31; Ub, ubiquitin; WT, wild type.